U. S. policy towards Iran: Developments, options and scenarios - Peter Rudolf (Stiftung Wissenschaft und Politik (SWP), 2005)
Even after the March 2005 European-American agreement on a common tactical approach to the conflict over Iran's nuclear ambitions, policy towards Iran remains a potential flash point in transatlantic relations. The Bush administration supports the negotiations, in which Great Britain, France and Germany want to move Iran towards voluntary self-restraint with respect to its civilian nuclear energy program. The administration will no longer block two concrete incentives the Europeans want to offer Iran: the prospect of membership in the World Trade Organization and the sale of spare parts for passenger aircraft. However, this step does not imply that the Bush admini-stration has changed course towards a policy of engagement. (SWP-Comments / SWP)
Keywords: 320